Eco-Friendly Asphalt Containing Recycled High-Density Polyethylene (HDPE): Performance Assessment and Cost Analysis - Yazdani, Leila; Hoornahad, Hooman; Akbarpour, Abbas (International Journal of Sustainable Construction Engineering and Technology, 2022)
Utilization of the recycled waste materials for new products is considered as a viable solution for saving the environment. This study paper targets the performance evaluation of hot-mix asphalt made with the modified bitumen 60/70 containing 3% and 5% of recycled high-density polyethylene (HDPE) (by the weight of optimum bitumen). First, the properties of modified bitumen mixtures including specific density, penetration depth, ductility, and softening point were measured. Then, the properties of asphalt mixtures made with the modified bitumen including rutting depth and resilient modulus were measured. Findings indicated the suitability of recycled HDPE available in Iranian market in the development of eco-friendly asphalt mixtures. Results showed a 49% decrease in penetration depth and a 15% increase in softening point for the suggested modified bitumen mixture containing 3% of recycled HDPE compared to those of control bitumen mixture, i.e. the bitumen mixture containing 0% of recycled HDPE. Results also showed a 47% decrease in rutting depth and a 113% increase in resilient modulus of asphalt made with the bitumen mixture containing 3% of recycled HDPE compared to those of control asphalt mixture, i.e. the asphalt mixture containing 0% of recycled HDPE. The results showed that the suggested asphalt mixture can be an appropriate option to be adopted not only in moderate climates but also in tropical climates as its characteristics become comparable to those of the bitumen 40/50 and the bitumen 30/40. Replacing a portion of bitumen by the recycled HDPE not only improves the characteristics of asphalt, but also has a positive impact on reducing the natural resource depletion and environmental pollution resulting from burning and/or the retention of plastic waste left in nature. The suggested eco-friendly asphalt is also cost effective.